Security and privacy of electronic healthcare records : concepts, paradigms and solutions (Institution of Engineering and Technology, 2019)
Presenting a detailed framework as well as comparative case studies for security protection, data integrity, privacy preservation, scalability, and healthcare legislation, this book covers state of the art research and addresses privacy and security methods and technologies for EHRs.
Keywords: Computer security.; Data protection.; Distributed databases.; elektronické knihy; electronic books